Uses and Gratification Theory in TikTok as Social Media Marketing Platform: Seen from Market Player View - Mutiara, Praventyasari; Kinkin Yuliaty Subarsa Putri (Journal of Digital Marketing and Communication, 2023)
This study aimed to understand the relationship between social media users and content using the use and gratification theories. It is also written to apprehend one of many communication theories, which includes mass communication theory and uses and gratification theory. This theory studies the reasons why people use social media platforms to create brand awareness and why they choose a particular platform to promote their brand awareness. The research methodology used in this study was descriptive qualitative. The author took samples from TikTok users who use social media to create brand awareness using the use and gratification theories. The research used two types of accumulation data technique (ADT), which are online desk research by interview and online desk research. TikTok was the mass media used for this research. The results show why TikTok is chosen as the best mass medium for creating brand awareness based on the uses and gratification theory. In conclusion, TikTok meets the qualifications for social media marketing to create brand awareness based on the uses and gratification theory.